ANALYSIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HASIL PEMERIKSAAN AUDIT SEKTOR PUBLIK (Studi Empiris pada BPKP Perwakilan Jawa Tengah) - Badjuri Achmad (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
The purpose of this research is to examine the effect of job experience, independence, objectivity, integrity, and competence on the quality of audit results at Representatives BPKP of Central Java. Job experience was measured by indicators the length of works as an auditor and the number of inspection tasks are performed. Independence was measured by indicators of independence in programming, in the execution of work, and independence in reporting.Objectivity was measured by indicator, free from conflict of interest and disclosure of factual conditions. Integrity was measured by indicator honesty, courege, prudence, and responsibility that auditors have. Competency was measured by indicator personal quality, general knowledge, and specialized expertise. While quality of audit results was measured by indicator of compliance with auditing standard and quality of examination report. The population of this study is civil servants whose work at Representatives BPKP of Central Java with sample is the civil servants has been following education and training as functional auditor. Data analysis was performed with multiple linear regression model. Test result showed that job experience, independence, and objectivity has no effect on quality of audit result at representatives BPKP of Central Java. While the integrity and competence have influence to quality of audit result at representatives BPKP of Central Java. Key words: job experience, independency, objectivity, integrity, competency, quality of audit result.